(1182) اختيار الاسلوب الفنى للإنتاج فى تصنيع البلاد النامية - حسن عبد العزيز حسن (معهد التخطيط القومى, 2026)
ملخص تتناول هذه المذكرة البحثية التي أعدها الدكتور حسن عبد العزيز حسن عام ١٩٧٦ قضية المفاضلة بين أساليب الإنتاج كثيفة العمالة وأساليب الإنتاج كثيفة رأس المال في الدول النامية التي تتسم بوفرة الأيدي العاملة وندرة رؤوس الأموال، وذلك في إطار التخطيط القومي الشامل. وتستعرض الدراسة المعايير الاقتصادية المختلفة للاختيار، موضحة التضارب القائم بين هدف تعظيم الناتج والعمالة الفورية من خلال التكنيك كثيف العمالة، وبين هدف تعظيم الفائض الاقتصادي القابل لإعادة الاستثمار لتحقيق نمو أسرع في الأجل الطويل عبر التكنيك كثيف رأس المال. ويبرز البحث أن اختيار الأسلوب الأمثل يتوقف بشكل جذري على الأهداف الاستراتيجية للدولة ومدى تفضيلها للنتائج الراهنة مقابل المستقبلية، مع التأكيد على أن مستويات الأجور السائدة تؤثر مباشرة على كفاءة كل أسلوب في توليد الفائض اللازم للتراكم الرأسمالي. كما يتطرق الملف إلى تعقيدات العملية الإنتاجية والتشابكات المرتبطة بالتقدم الفني وتطويع التكنولوجيا المستوردة لتلائم الواقع المحلي، محللاً أثر الاختيارات الفنية على متغيرات اقتصادية حيوية مثل ميزان المدفوعات، والطلب على الغذاء، ومعدلات التضخم، والنمو السكاني. وتبين الدراسة أن التحليل الجزئي لكل مشروع على حدة لا يكفي لاتخاذ القرار السليم، بل يجب النظر إلى الاقتصاد ككل لضمان التوازن بين معدلات الاستهلاك والادخار، وتجنب الارتداد إلى مستويات التخلف السابقة. وتخلص المذكرة إلى ضرورة بناء قاعدة علمية وتقنية وطنية قادرة على غربلة وتطوير أساليب الإنتاج بما يخدم مصلحة الاقتصاد القومي ويحقق التنمية المستدامة بعيداً عن التبعية التكنولوجية المطلقة. This research paper, prepared by Dr. Hassan Abdel Aziz Hassan in 1976, addresses the issue of choosing between labor-intensive and capital-intensive production methods in developing countries characterized by an abundance of labor and a scarcity of capital, within the framework of comprehensive national planning. The study reviews the various economic criteria for this choice, highlighting the inherent conflict between the objective of maximizing output and immediate employment through labor-intensive techniques, and the objective of maximizing economic surplus that can be reinvested to achieve faster long-term growth through capital-intensive techniques. The research emphasizes that choosing the optimal method depends fundamentally on the strategic objectives of the state and its preference for present versus future outcomes, while also stressing that prevailing wage levels directly influence the efficiency of each method in generating the surplus necessary for capital accumulation . The report also addresses the complexities of the production process and the interconnections associated with technological advancements and adapting imported technology to suit local realities. It analyzes the impact of technological choices on vital economic variables such as the balance of payments, food demand, inflation rates, and population growth. The study demonstrates that a piecemeal analysis of each project individually is insufficient for sound decision-making; rather, the economy as a whole must be considered to ensure a balance between consumption and savings rates and to avoid a regression to previous levels of underdevelopment. The report concludes by emphasizing the necessity of building a national scientific and technological base capable of evaluating and developing production methods in a way that serves the national economy and achieves sustainable development, free from absolute technological dependence .